Flame Atomic Absorption Spectrometric Determination of Trace Amounts of Silver after Solid-Phase Extraction with 2-Mercaptobenzothiazole Immobilized on Microcrystalline Naphthalene. (23rd May 2013) - Shakerian, Farid; Haji Shabani, Ali Mohammad; Dadfarnia, Shayessteh; Shabani, Mahdieh
Abstract : A simple and sensitive solid-phase extraction (SPE) procedure combined with flame atomic absorption spectrometry (FAAS) was designed for the extraction and determination of trace amounts of silver. A column of immobilized 2-mercaptobenzothiazole (MBT) on microcrystalline naphthalene was used as the sorbent. Silver was quantitatively retained on the column in the pH range of 0.5–6.0. After extraction, the solid mass consisting of silver complex and naphthalene was dissolved out of the column with 5.0 mL of dimethylformamide, and the analyte was determined by flame atomic absorption spectrometry (FAAS). Under the optimum experimental conditions, the adsorption capacity was found to be 1.18 mg of silver per gram of the sorbent. A sample volume of 800 mL resulted in a preconcentration factor of 160. The relative standard deviation obtained for ten replicate determinations at a concentration of 0.8 µg L −1 was 1.4%, and the limit of detection was 0.02 µg L −1 . The method was successfully applied to the determination of silver in radiology film, waste water, and natural water samples. The accuracy was examined by recovery experiments, independent analysis by electrothermal atomic absorption spectrometry, and analysis of two certified reference materials.